Operating Expenses Operating Income Impact on Financial Performance Conventional Banks in Indonesia - Safitri, Ayu; Machmuddah, Zaky (Journal of Applied Accounting and Taxation, 2025)
This study aims to empirically prove the moderating role of Loan to Deposit Ratio (LDR) on the effect of Capital Adequacy Ratio (CAR) and Operating Cost of Operating Income (BOPO) on financial performance and proxied by Return on Assets (ROA). All banks in Indonesia are the population of this study. The sample is only of conventional banks that meet the specified criteria. WarpPLS version 7.0 was used as the data analysis tool. The results of this study show that only BOPO has an impact on ROA. CAR does not affect ROA, and LDR has no moderating effect on the relationship. This study implies that conventional banks in Indonesia should pay attention to BOPO because it influences ROA, which can affect the investment decisions of potential investors and investors.